2007
DOI: 10.1124/mol.107.037465
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/Enhancer Binding Protein Homologous Protein-Dependent Death Receptor 5 Induction and Ubiquitin/Proteasome-Mediated Cellular FLICE-Inhibitory Protein Down-Regulation Contribute to Enhancement of Tumor Necrosis Factor-Related Apoptosis-Inducing Ligand-Induced Apoptosis by Dimethyl-Celecoxib in Human Non–Small-Cell Lung Cancer Cells

Abstract: 2,5-Dimethyl-celecoxib (DMC) is a derivative of celecoxib, a cyclooxygenase-2 (COX-2) inhibitor with anticancer activity in both preclinical studies and clinical practice, and lacks COX-2-inhibitory activity. Several preclinical studies have demonstrated that DMC has better apoptosis-inducing activity than celecoxib, albeit with undefined mechanisms, and exhibits anticancer activity in animal models. In this study, we primarily investigated DMC's cooperative effect with tumor necrosis factor-related apoptosis-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 34 publications
4
48
2
Order By: Relevance
“…There are several reports indicating a synergistic apoptotic response achieved by the combination of TRAIL with chemotherapeutic drugs (13,14). Increased apoptotic rates in a variety of cancer cell lines have also been reported after the combination of TRAIL with proteasome inhibitors resulting by augmentation of DR5 protein levels (15)(16)(17)(18)(19)(20)(21)(22)(23). Although the role of DR5 up-regulation and involvement in TRAIL-induced sensitization to apoptosis by proteasome inhibitors is well documented, the mechanism by which DR5 is up-regulated is not known and is the subject of the present investigation.…”
Section: Inhibition Of Yin Yang 1-dependent Repressor Activity Of Dr5mentioning
confidence: 99%
“…There are several reports indicating a synergistic apoptotic response achieved by the combination of TRAIL with chemotherapeutic drugs (13,14). Increased apoptotic rates in a variety of cancer cell lines have also been reported after the combination of TRAIL with proteasome inhibitors resulting by augmentation of DR5 protein levels (15)(16)(17)(18)(19)(20)(21)(22)(23). Although the role of DR5 up-regulation and involvement in TRAIL-induced sensitization to apoptosis by proteasome inhibitors is well documented, the mechanism by which DR5 is up-regulated is not known and is the subject of the present investigation.…”
Section: Inhibition Of Yin Yang 1-dependent Repressor Activity Of Dr5mentioning
confidence: 99%
“…9). Although FLIP ubiquitination has been detected in several cell subtypes (16)(17)(18), the precise mechanism underlying FLIP ubiquitination was not determined. In the present study, we show for the first time that Itch binds to FLIP S and FLIP L to facilitate FLIP ubiquitination in a time-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…For example, specific agents, such as dimethyl-celecoxib and 5,7-dimethoxyflavone, have been shown to induce the expression of DR5 via CHOP-dependent DR5 gene transactivation (18,19). Furthermore, previous studies have identified a close association between DR5 expression and ER stress (10,17).…”
Section: Discussionmentioning
confidence: 99%